Suprimento de potássio em argissolo com histórico de adubação potássica - Kist, Sinval Ledur (2005)
In some soils with low amount of exchangeable potassium (Kt), the plants uptake amounts larger than the available ones, suggesting that nonexchangeble forms (Knt) participate in the plants supply. As use K fertilization to upper the soil potassium availability, two experiments was carried out to understand (a) the dynamics of K release in a ultisol, with a history of K additions, (b) submit a soil sample to five successive greenhouse crops, and (c) evaluate the efficiency of added K a soybean and wheat yield. The original soil was submitted to K fertilization, until 1991, treated with 0, 720, 900 and 1080 kg ha-1 K2O, splitting over on twelve years. In the greenhouse experiment, the soil used in the pots was collected from the field experiment in the 0-10 cm of the portions witness and in that that received the largest potassium rate, which presented amounts of 28 and 80 mg K kg-1, respectively. The soil was dried, drizzled and conditioned in pots with 3 Kg and later built a gradient for both initial amounts being added the rate 0, 10 and 30 mg K soil kg-1 up to the third cultivation, and 0, 20 and 60 in the last two cultivations. The fertilization with phosfate and micronutrients was accomplished in the beginning of the experiment and after the third cultivation. Successive cultivations of oats, wheat, soybean, corn and beans, were done in the greenhouse, which were collected when the plants were with the flower, droughts, carry weigh, undergone digestion and determinaded of absorbed potassium. After each cultivation, a soil sample was collected for the analyses with the Mehlich 1, HNO3 boiling 1mol L-1, NaBPh4 and acid digestion extractors. The statistical analysis was accomplished with the analysis of the variance of the levels of K added on the production of dry matter, amounts of absorbed K and the extracted amounts with the Mehlich 1, HNO3 boiling 1mol L-1 and NaBPh4 extractors, and the effect of the levels of K on the soil A1 and A2. The amounts of absorbed K for the cultivations and extracted for the Mehlich 1, HNO3 boiling 1mol L-1, NaBPh4 and acid digestion extractors, it took place the lineal correlation of Pearson (p>0,05). The field experiment was carried out with the cultivation of soybean 2003/04 and wheat 2004. The culture of the soybean was fertilized with 100kg of P2O5 ha-1 in the sowing line, while for the wheat 50kg P2O5 was used ha-1 and 22kg N, and 40kg N in covering. The harvest of the cultures took place in an area of 8m2 in each sub-portion, the grains were weighed and the humidity corrected for 13%. After each cultivation soil samples were collected in the 0-10cm depth in each sub-portion and they were determined the amounts K with the extractor of Mehlich 1. The statistical procedure used was the analysis of the variance and adjustment of regressions polinomiais to the averages. The production of dry matter and the amounts of absorbed K in the cultivations demonstrated that there was significant difference at the levels of added K. Interaction was not observed between the levels of added K and the soils A1 and A2 for most of the cultivations. The extractors are shown appropriate for prediction of K accessed by the plants, this must have happened because all the forms of the soil seem to contribute concomitant for the supply of K to the plants. The productivity of soybean grains in response to addition of K is verified when occurs frequent additions and in small rate, independent of solid additions in previous years, with the objective of increasing the levels of K in the soil and in production. The production of wheat grains in succession the soybean obeys the same pattern of readiness, but the prior applications may characterize a carry over enough to reach satisfactory wheat production. The capacity of soil potassium supply depends more on its mineralogical characteristics than of its report of fertilization.